The father is dead! Long live the father! - Hook, Derek (PINS-Psychology in Society, 2015)
Lacan, Jacques (2013) The triumph of religion. (Translated by Bruce Fink). Cambridge: Polity Press. ISBN 978-0-745-65989-3 hbk. Pages 92